Monetary Ease: A Factor behind Financial Crises? Some Evidence from OECD Countries - Rudiger Ahrend (Kiel Institute for the World Economy (IfW), 2008)
This paper addresses the question of whether and how easy monetary policy may lead to excesses in financial and real asset markets and ultimately result in financial dislocation. It presents evidence suggesting that periods when short-term interest rates have been persistently and significantly below what Taylor rules would prescribe are correlated with increases in asset prices, especially as regards housing, though no systematic effects are identified on equity markets. Significant asset price increases, however, can also occur when interest rates are in line with Taylor rules, associated with periods of financial deregulation and/or innovation. The paper argues that accommodating monetary policy over the period 2002-2005, in combination with rapid financial market innovation, would seem in retrospect to have been among the factors behind the run-up in asset prices and financial imbalances – the (partial) unwinding of which helped trigger the 2007/08 financial market turmoil.
Keywords: E5; G15; F3; E44; 330; Interest rates; monetary policy; housing; sub-prime crisis; financial markets; macro-prudential; regulation Taylor rule; house prices; Geldpolitik; Finanzmarkt; Finanzmarktkrise; Zins; Taylor-Regel; Immobilienpreis; Vermögen; Bubbles; OECD-Staaten